Role of Auxin in Maize Endosperm Development (Timing of Nuclear DNA Endoreduplication, Zein Expression, and Cytokinin). - Lur, H. S. (1993)
The timing of developmental events and regulatory roles of auxin were examined in maize (Zea mays L.) endosperms. Zeatin, zeatin riboside, and indole-3-acetic acid (IAA) levels were determined by enzyme-linked immunosorbent (ELISA). Zeatin and zeatin riboside increased to maximal concentrations at an early stage (9 d after pollination [DAP]), corresponding to the stage when cell division rate was maximal. In contrast, IAA concentration was low at 9 DAP and abruptly increased from 9 to 11 DAP, thus creating a sharp decline in the cytokinin to auxin ratio. Coincident with the increase in IAA was an increase in DNA content per nucleus, attributed to postmitotic DNA replication via endoreduplication. Exogenous application of 2,4-dichlorophenoxyacetic acid (2,4-D) at 5 or 7 DAP hastened the time course of DNA accumulation per nucleus and increased the average nuclear diameter, whereas 2-(para-chlorophenoxy)isobutyric acid delayed such development. Exogenously applied 2,4-D hastened the accumulation of the zein polypeptides of apparent molecular masses of 12, 14, and 16 kD and the expression of mRNA hybridizing with a zein DNA probe. We conclude that an abrupt increase in auxin induces cellular differentiation events in endosperm, including endoredupliction and expression of particular zein storage proteins.